Contraception pathway: application for midlife women - Chi-Son Kim; Deanna Tikhonov; Lena Merjanian; Adrian C. Balica (BMC, 2017)
Abstract Objective To create a system where evidence based medicine can be applied to accommodate every woman's needs by designing a contraceptive pathway that can be utilized by any healthcare provider, regardless of the patient's age, and to offer appropriate counseling in order to maximize patient outcomes, especially for the midlife woman. Methods United States Medical Eligibility Criteria for Contraceptive Use, 2016 (US MEC) was used as the framework for these recommendations for a contraceptive care pathway that can be incorporated into care for midlife women. Discussion By utilizing a total office approach that includes the scheduler, receptionist, medical assistant, nurse and health care provider as members of a team, the entire spectrum of the patient population in need of contraception from teenagers to midlife can be captured. Specifically for midlife women the need for an effective form of contraception may be overlooked as fecundity declines in this age group. This paper will highlight the use of this pathway for midlife women.